The Effect of Health Education on Anemia Prevention (HB Levels) in Pregnant Women in the Third Trimester - Sri Hariati; Anik Sri Purwanti (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Anemia among pregnant women remains a significant public health concern in Indonesia, contributing to adverse maternal and fetal outcomes such as preterm birth, low birth weight, and impaired fetal development. The third trimester represents a critical stage, as iron requirements increase substantially due to rapid fetal growth and expanded maternal blood volume. Insufficient hemoglobin (HB) levels during this period are closely linked to negative health outcomes, highlighting the need for effective prevention strategies. Health education has been widely recognized as an important intervention to enhance knowledge, attitudes, and practices related to nutrition, iron supplementation, and anemia prevention. This study aimed to examine the effect of health education on anemia prevention by assessing hemoglobin levels in third-trimester pregnant women. A quantitative pre-experimental design with a one-group pretest-posttest approach was applied to 30 participants selected through purposive sampling. Hemoglobin levels were measured before and after structured health education sessions covering anemia prevention, iron tablet adherence, dietary improvement, and healthy lifestyle practices. Data were analyzed using the Wilcoxon signed-rank test with a significance level of p < 0.05. The findings showed a significant increase in hemoglobin levels after the intervention (p = 0.000). These results indicate that structured health education effectively improves hemoglobin levels and supports anemia prevention in pregnant women.